2022
DOI: 10.1038/s42003-022-03676-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome of the mouse retinal pigment epithelium in response to a low-dose of doxorubicin

Abstract: Cellular senescence of the retinal pigment epithelium (RPE) is thought to play an important role in vision-threatening retinal degenerative diseases, such as age-related macular degeneration (AMD). However, the single-cell RNA profiles of control RPE tissue and RPE tissue exhibiting cellular senescence are not well known. We have analyzed the single-cell transcriptomes of control mice and mice with low-dose doxorubicin (Dox)-induced RPE senescence (Dox-RPE). Our results have identified 4 main subpopulations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Then, the major cell types were assigned to each cluster based on the expression levels of known marker genes (Supplementary Figure 32b, Supplementary Data 1). , Since gene expression was affected little by treatment with Mito-K2 in the control mice (Supplementary Figure 34f), the control, Alu , and Mito-K2-groups were included in the subsequent analysis. Among all the cells, 10,531 RPE cells were identified according to the expression of RPE-specific markers, including Rpe65 (Con-RPE: 3424, Alu -RPE: 3587, and Mito-K2-RPE, 3520).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, the major cell types were assigned to each cluster based on the expression levels of known marker genes (Supplementary Figure 32b, Supplementary Data 1). , Since gene expression was affected little by treatment with Mito-K2 in the control mice (Supplementary Figure 34f), the control, Alu , and Mito-K2-groups were included in the subsequent analysis. Among all the cells, 10,531 RPE cells were identified according to the expression of RPE-specific markers, including Rpe65 (Con-RPE: 3424, Alu -RPE: 3587, and Mito-K2-RPE, 3520).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to better characterize the cellular senescence of RPE cells in a GA mouse model induced by Alu RNA and appropriate monitoring of the senescent RPE cells clearance, we tried to establish a panel of genes. First, considering the enormous molecular diversity between cell types, we included genes that were significant in our recent study using Dox-induced RPE senescence model . The twelve ‘senescence/RPE panel’ genes identified in the analysis were as follows: a senescence core gene (Cdkn1a), genes associated with cellular senescence (A2m, Ntrk2, Malat1), SASP component genes (Serping1, Tmem176b, Gas6), genes associated with the regulation of apoptosis (Ckmt1, Ccng1), genes related to the extracellular matrix (ECM) or epithelial-mesenchymal transition (EMT) of RPE (Timp1, Vim), and a gene associated with drusen biogenesis in AMD (Clu) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our present transcriptomic analysis demonstrated an incomplete ability to separate the RPE cell transcriptomic profiles based solely on time, pointing out the need to dissect RPE cellular heterogeneity at each timepoint. Recent studies using single cell approaches have reported multiple RPE subpopulations within the stem cell-derived, native human and mouse RPE with unique transcriptional and morphological characteristics, indicating that the RPE cell layer is composed of heterogenous cell populations that may have differing functional and clinical capabilities (Lee et al, 2022; Petrus-Reurer et al, 2022; Voigt et al, 2019; Xu et al, 2021). Identification of the subpopulations responsible for vision rescue can improve regulatory evaluation and improve RPE cell products to result in better transplantation outcomes.…”
Section: Discussionmentioning
confidence: 99%